2021
DOI: 10.3390/ma14051302
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic Ash as a Sustainable Binder Material: An Extensive Review

Abstract: The construction industry is affected by the constant growth in the populations of urban areas. The demand for cement production has an increasing environmental impact, and there are urgent demands for alternative sustainable solutions. Volcanic ash (VA) is an abundant low-cost material that, because of its chemical composition and amorphous atomic structure, has been considered as a suitable material to replace Portland cement clinker for use as a binder in cement production. In the last decade, there has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 95 publications
(254 reference statements)
2
14
0
Order By: Relevance
“…Most are in Alaska, but they are across the U.S. as well. Harvesting this material is not damaging to the Earth in the same way that lime mining is, and the process for refining this ash to be useable in concrete does not release the same amount of carbon as Portland cement or burning coal [26,27].…”
Section: Synopsis Of Existing Literaturementioning
confidence: 99%
“…Most are in Alaska, but they are across the U.S. as well. Harvesting this material is not damaging to the Earth in the same way that lime mining is, and the process for refining this ash to be useable in concrete does not release the same amount of carbon as Portland cement or burning coal [26,27].…”
Section: Synopsis Of Existing Literaturementioning
confidence: 99%
“…Many research groups and corporations are dealing with the preparation of concrete from volcanic ash, fly ash, blast furnace slag, silica fume, metakaolin, or pumice, etc. [18][19][20][21]. These research studies have shown that the Portland cement replacement leads to improved material properties of the resulting concrete mixture including diffusive parameters that are involved in durability analysis and, therefore, these mixtures are more suitable.…”
Section: Introductionmentioning
confidence: 99%
“…Pozzolanic materials are utilized as SCMs with PC and are generally categorized according to their sources as natural or artificial substances. Natural pozzolanic materials can be available in the form of huge untapped deposits all over the world 10 .…”
Section: Introductionmentioning
confidence: 99%